Designing A Zener Diode Using Ag2O(1-X)Zno(X)/Psi Structures Deposited by Laser Induced Plasma Technique - Jamal, Raied K.; Ali, Falah Hassen; Hameed, Mohammed M.; Aadim, Kadhim Abdulwahid (Iraqi Journal of Science, 2020)
In this paper Zener diode was designed by mixing three mixing ratios of Ag2O(1-x)ZnO(x), where x is 0.5, 0.3, and 0.1, that are deposited on a p-type porous silicon using laser induced plasma technique at room temperature (RT). The results of the Zener diode showed a decrease in knee and Zener voltage when the mixing ratio of Ag2O(1-x)ZnO(x) structure was increased. Nanofilms of 200nm thickness were prepared from pure ZnO and Ag2O as well as Ag2O(1-x)ZnO(x) with three maxing ratios and deposited on glass slides at RT to analyze the structure and optical properties. The structures of Ag2O and Ag2O(1-x)ZnO(x) showed high absorbance in the visible region with redshift in spectra when the mixing ratio was increased, while ZnO had a high absorbance in the ultraviolet region. It is concluded that when the value of x increases the energy gap value for the Ag2O(1-x)ZnO(x) structure decreases.